Muslims and crusaders Christianity's wars in the Middle East, 1095-1382, from the Islamic sources - hristie, Niall (Routledge, 2020)
"Muslims and Crusaders combines chronological narrative, discussion of important areas of scholarly enquiry and evidence from Islamic primary sources to give a well-rounded survey of Christianity's wars in the Middle East, 1095-1382. Revised, expanded and updated to take account of the most recent scholarship, this second edition enables readers to achieve a broader and more complete perspective on the crusading period by presenting the crusades from the viewpoints of those against whom they were waged, the Muslim peoples of the Levant. Engaging with a wide range of translated primary source documents, including chronicles, dynastic histories, religious and legal texts, and poetry, Muslims and Crusaders is ideal for students and historians of the crusades"